The Intriguing Nexus between Corruption and Capital Account Restrictions - Axel Dreher; Lars-H. R. Siemers (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
The paper develops a theoretical model showing a mutual relationship between corruption and capital account restrictions. According to the model, higher corruption induces stricter restrictions and vice versa. We test the model using panel data for 112 countries over the period 1984?2002 and find that corruption and restrictions are indeed mutually determined. Estimating the model simultaneously, capital account restrictions induce higher corruption. Higher corruption, in turn, is associated with more restrictions on the capital account.The empirical relationship is,however, not completely robust.
Keywords: O17; C33; H26; D19; G11; F33; 330; Corruption; capital account restrictions; dynamic panel; Korruption; Kapitalbilanz; Kapitalverkehrspolitik; Schätzung